Kewajiban Nafkah Ayah Bagi Anak Pasca Penceraian Perspektif Hukum Keluarga Islam Dan Hukum Perdata - Saini Saini; Ifadatul Hosniah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2021)
Every human being is created in pairs between a man and a woman, thus forming a marital relationship. But navigating the marriage ship will not go the way you want it to, with divorce sometimes being a shortcut in the marital relationship. Divorce in marriage will have many repercussions, including raising children after divorce. As child support is often overlooked by heirs to their rights and obligations, Islamic law and civil law provide for alimony during marriage or after marriage (divorce). The methodology of this research uses a normative juridical approach and the type of research is library research. Then the primary data sources used are Islamic Family Law and Civil Law. The secondary data sources used are books related to problem formulation and discussion. The data validity testing technique in this research uses data source triangulation. The result of this study is that child maintenance after divorce according to Islamic family law is fully borne by the father, but this obligation can be reduced, if the father cannot work for a living (paralyzed, etc.) and does not have a trump card to give. Meanwhile, child maintenance after divorce according to the provisions of civil law is the responsibility of both parents.